Menavigasi Politik Maritim: Tinjauan Sistematis dan Pemetaan Bibliometrik - Murtasidin, Bahjatul; Pratama, Sandy; Saputra, Putra Pratama (Jurusan Ilmu Politik Universitas Bangka Belitung, 2026)
Maritime affairs constitute a strategic domain within contemporary geopolitical dynamics. In recent decades, maritime spaces have ascended as a critical arena for power projection, driven by intensifying global competition. This study employs a systematic mapping approach to delineate the evolution and predominant research trends within maritime political studies. Utilizing bibliographic data from the Scopus database in the period of 2005–2025, we analyzed a corpus of scientific articles on maritime politics. The data were processed using the VOSviewer software to generate a network map of keywords, elucidate inter-topic relationships, and trace conceptual developments. The analysis reveals five dominant keywords that form the discursive core: marine policy, governance, the marine environment, ocean governance, and marine governance. These themes are not isolated but are intricately interconnected within a conceptual network, illustrating the trajectory of maritime politics over the past two decades. The inter topic relationships signify the integration of ecological and political imperatives, shaping an emergent governance model characterized by its trans boundary, collaborative, and sustainability-oriented nature. This evolution represents an epistemological shift from a state-centrist paradigm, through a governance paradigm, toward a nascent ecological-political paradigm. Consequently, the sea is no longer conceived merely as an economic or territorial domain, but is increasingly recognized as a complex and dynamic political space.